Circadian and Neuroendocrine Basis of Photoperiodism Controlling Diapause in Insects and Mites: A Review - Takeda, Makio; Suzuki, Takeshi (Frontiers in Physiology, 2022)
Photoperiodic system is concealed in the highly complex black-box, comprising four functional subunits: 1) a photo/thermo-sensitive input unit, 2) a photoperiodic clock based on a circadian system, 3) a condenser unit counting the number of inductive signals, and 4) a neuroendocrine switch that triggers a phenotypic shift. This review aims to summarize the research history and current reach of our understanding on this subject to connect it with the molecular mechanism of circadian clock rapidly being unveiled. The review also focuses on the mode of intersubunit information transduction. It will scan the recent advancement in research on each functional subunit but special attention will be given onto the circadian clock-endocrine conjunct and the role of melatonin signaling in the regulation of insect photoperiodism. Prothoracicotropic hormone (PTTH) probably plays the most crucial role in the regulation of pupal diapause. Search for the trigger to release the PTTH hit some candidates, i.e., indoleamines in Antheraea pernyi. Indolamine metabolism is controlled by arylalkylamine N-acetyltransferase (aaNAT). Indolamine dynamics and aaNAT enzymatic activity changed according to photoperiods. aaNAT activity and melatonin content in the brain showed not only a photoperiodic response but also showed a circadian fluctuation. aaNAT had multiple E-boxes, suggesting that it is a clock-controlled-gene (ccg), which implies that cycle (cyc, or brain–muscle Arnt-like 1 = Bmal1)/Clock (Clk) heterodimer binds to E-box and stimulates the transcription of aaNAT, which causes the synthesis of melatonin. RNAi against transcription modulators, cyc or Clk down-regulated aaNAT transcription, while RNAi against repressor of cyc/Clk, per upregulated aaNAT transcription. Surprisingly immunohistochemical localization showed that the circadian neurons carry epitopes of melatonin producing elements such as aaNAT, the precursor serotonin, HIOMT and melatonin as well as clock gene products such as cyc-ir, Per-ir, and dbt-ir , while PTTH-producing neurons juxtaposing to the clock neurons showed hMT2-ir in A. pernyi brain. Melatonin probably binds to the putative melatonin receptor that stimulates Ca2+ influx, which in turn activates PKC. This induces Rab 8 phosphorylation and exocytosis of PTTH, leading to termination of diapause. All the PTTH-expressing neurons have PKC-ir, and Rab9-ir. When diapause is induced and maintained under short days, serotonin